2019
DOI: 10.4067/s0718-07642019000500003
|View full text |Cite
|
Sign up to set email alerts
|

Granulometría, Propiedades Funcionales y Propiedades de Color de las Harinas de Quinua y Chontaduro

Abstract: El propósito de este estudio fue realizar la determinación de las propiedades granulométricas, funcionales y de color de la harina de quinua y de chontaduro. La quinua y el chontaduro poseen grandes atributos nutricionales, sensoriales y son substitutos potenciales del trigo en la elaboración de diversos alimentos. Sin embargo, existen pocas publicaciones sobre las propiedades funcionales y físicas de sus harinas. Sus propiedades fueron determinadas y a los datos se aplica estadística descriptiva, ANOVA y la p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
3
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
1
3
3
5
Order By: Relevance
“…The SP of the flours is influenced by the particle size, the variety of species, and the method of processing or obtaining [ 42 ]. These results are superior to those reported by Dussán-Sarria et al [ 44 ] found SP values for quinoa and peach palm fruit flours of 4.43 and 2.64 mL/g, respectively.…”
Section: Resultscontrasting
confidence: 99%
“…The SP of the flours is influenced by the particle size, the variety of species, and the method of processing or obtaining [ 42 ]. These results are superior to those reported by Dussán-Sarria et al [ 44 ] found SP values for quinoa and peach palm fruit flours of 4.43 and 2.64 mL/g, respectively.…”
Section: Resultscontrasting
confidence: 99%
“…Higher values of a * and b * correspond to higher Chroma values. The H * coordinate represents the true color, effective in showing the color appearance of food products (Dussán-Sarria et al, 2019). In this study, the value of C * increased with the increment in the proportion of DCP.…”
Section: Color Of the Floursmentioning
confidence: 54%
“…Las propiedades funcionales están influenciadas por la interacción de los componentes de la harina con el agua (Dussán-Sarria et al, 2019). La CAA y la CH predicen la calidad de harinas panaderas en tanto macromoléculas como carbohidratos, proteínas y almidón dañado aumentan la retención de agua al proporcionar cadenas laterales hidrofílicas (Ghumman et al, 2021;Pellegrini et al, 2018).…”
Section: Propiedades Funcionalesunclassified